Carbon fiber felt with silicon carbide coating on surface and preparation method thereof

By preparing silicon carbide coatings on the surface of carbon fiber felt and adopting a multi-layer coating design, the problem of carbon fiber felt being susceptible to erosion and insufficient interface binding force in harsh chemical environments is solved, and the effect of improving its chemical stability and mechanical properties is achieved.

CN119877270APending Publication Date: 2025-04-25ZHEJIANG HUAXIN NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510189038.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-20
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Carbon fiber felt is susceptible to chemical erosion in harsh chemical environments, and its interface bonding force with other materials is not strong, resulting in a decrease in mechanical properties and a shortened service life.

Method used

By preparing a silicon carbide coating on the surface of the carbon fiber felt, the bonding force between the carbon fiber felt and the silicon carbide coating is enhanced by using a silane coupling agent hydrolysis reaction and a multi-layer coating design.

Benefits of technology

It significantly improves the chemical stability, mechanical properties and interface binding force of carbon fiber felt, extends the service life, and broadens its application areas.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a carbon fiber felt with a silicon carbide coating on the surface and a preparation method of the carbon fiber felt. The method comprises the following steps: pretreating the carbon fiber felt, mixing with a coupling agent solution, forming a precursor solution, dipping, coating components of a transition layer and the silicon carbide coating, pyrolyzing, curing and the like. Wherein during preparation of the coupling agent solution, a hydrolysis reaction is carried out, a hydrochloric acid catalyst is added, and ethanol and ethylene glycol are added as stabilizers; tetraethoxysilane and cane sugar are adopted as a silicon source and a carbon source, and preparation of a precursor solution is optimized; the transition layer and the silicon carbide coating are prepared and coated according to specific steps and proportions. According to the invention, the problems of weak binding force between the coating and the carbon fiber felt, uneven performance and the like are solved, the chemical stability and the mechanical property are enhanced, the heat resistance and the wear resistance of the material are improved, the coating structure is optimized, and the application field of the carbon fiber felt is widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite material preparation, in particular to a carbon fiber felt with a silicon carbide coating on the surface and a preparation method thereof. Background Art

[0002] As an important high-performance material, carbon fiber felt has broad application prospects in many fields such as aerospace, automobile, energy, and chemical industry because of its advantages such as high strength, high modulus, low density and excellent heat resistance.

[0003] However, in practical applications, carbon fiber felt itself has poor chemical stability. In harsh chemical environments, such as those with acid, alkali, high humidity or corrosive gases, carbon fiber is susceptible to chemical corrosion, which can lead to a decrease in its mechanical properties, thus affecting its service life and structural integrity. Secondly, the surface of carbon fiber felt is relatively smooth and has a low surface energy, which makes the interface bonding force weak when combined with other materials. When used together with other materials to form composite materials, the interface bonding is prone to weak, which greatly limits the application of carbon fiber felt in some fields that require high material bonding performance.

[0004] In order to improve the performance of carbon fiber felt, silicon carbide coating is introduced as a means of surface modification. Silicon carbide is a ceramic material with high hardness, high chemical stability, high wear resistance, good thermal stability and high temperature strength. Its application can effectively improve the comprehensive performance of the base material. Coating silicon carbide coating on the surface of the material can significantly improve the wear resistance, corrosion resistance and high temperature resistance of the material, providing an effective way for the development of high-performance materials. At present, there are some technologies for preparing silicon carbide coating on the surface of carbon fiber felt, but there are still many problems. In some existing technologies, the bond between silicon carbide coating and carbon fiber felt is not strong enough, and the coating is easy to peel off. This is mainly because the carbon fiber felt and silicon carbide coating are of different materials, and the interface bonding force between the two is weak. They often rely only on weaker forces such as physical adsorption, which causes the coating to peel off and peel off during use, affecting the performance and life of the product.

[0005] Therefore, it is necessary to provide a carbon fiber felt having a silicon carbide coating on the surface and a preparation method thereof to solve the above technical problems. Summary of the invention

[0006] The purpose of the present invention is to provide a carbon fiber felt with a silicon carbide coating on the surface and a preparation method thereof, so as to solve the problems that the activity of the hydrolysis product of the silane coupling agent is difficult to maintain, the storage stability of the hydrolysis product is poor, and the design of the transition layer and the silicon carbide coating is not reasonable enough to achieve a better gradient structure, resulting in an unsmooth performance transition between different layers, large internal stress and delamination risk.

[0007] To achieve the above object, the present invention provides the following technical solution: a method for preparing a carbon fiber felt having a silicon carbide coating on its surface, comprising the following steps: (1) Pre-treating the carbon fiber felt by first washing it with an organic solvent and then drying it under the protection of an inert gas; (2) mixing the pretreated carbon fiber felt with the coupling agent solution so that the coupling agent is evenly distributed on the surface of the carbon fiber felt; (3) dissolving a silicon source and a carbon source in a solvent to form a precursor solution, wherein the molar ratio of the silicon source to the carbon source is 1:1-5; (4) impregnating the carbon fiber felt treated with the coupling agent in step (2) into the precursor solution prepared in step (3); (5) sequentially coating the transition layer component and the silicon carbide coating component onto the carbon fiber felt treated by dip coating in step (4); (6) subjecting the coated carbon fiber felt in step (5) to pyrolysis treatment under inert gas protection, with the pyrolysis temperature set at 1000-1500° C. and the pyrolysis time maintained at 1-5 h, so that the precursor is converted into a silicon carbide coating; (7) Curing the carbon fiber felt after pyrolysis in step (6).

[0008] Preferably, in step (1), the organic solvent is ethanol, and the carbon fiber felt is completely immersed in the ethanol solution for 15-30 minutes.

[0009] Preferably, in step (1), a drying furnace protected by inert gas is used, the cleaned carbon fiber felt is placed in the drying furnace, and the inert gas is continuously introduced to maintain an inert atmosphere in the furnace at a temperature of 50-100°C.

[0010] Preferably, in step (2), the coupling agent solution is a silane coupling agent solution, and an amino-containing silane coupling agent (KH-550) is dissolved in ethanol, and stirred at a stirring speed of 200-500 r / min for 15-30 min to prepare a silane coupling agent solution with a mass fraction of 0.5%-5%, and the carbon fiber felt is immersed in the silane coupling agent solution for 0.5-2 h, and stirred at a speed of 50-100 r / min during the immersion process.

[0011] Preferably, in step (2), the coupling agent solution is a silane coupling agent solution. Before the solution is prepared, an aminosilane coupling agent (KH-550) is added to a mixed solution of isopropanol and water for hydrolysis reaction, the volume ratio of alcohol to water is 2:1, the stirring speed is 400-500 r / min, the stirring time is 30-60 min, and the reaction temperature is between 30-40°C; and hydrochloric acid is added as a catalyst, and the amount of the catalyst added is 0.5%-0.7% of the mass of the silane coupling agent.

[0012] Preferably, in step (2), ethanol and ethylene glycol are added to the hydrolyzate as stabilizers, ethanol is added first in an amount of 7%-8% of the volume of the hydrolyzate, and stirred evenly at a stirring speed of 450 r / min for 10-15 min; ethylene glycol is then added in an amount of 10%-12% of the volume of the hydrolyzate, and stirring is continued during the addition process.

[0013] Preferably, in step (3), the silicon source is tetraethyl orthosilicate, the carbon source is sucrose, and the solvent is at least two of ethanol, isopropanol, and water; a container with a stirring function is used to hold the solvent, and tetraethyl orthosilicate and sucrose are added to the solvent at a stirring speed of 400-500 r / min and a stirring time of 45-60 min.

[0014] Preferably, in step (5), the transition layer comprises, by weight: 2 parts of epoxy-containing silane coupling agent (KH-560), 6 parts of phenyl silicone resin, and 2 parts of nano-silicon dioxide particles; Dissolve the transition layer components in ethanol to form a transition layer solution, immerse the carbon fiber felt treated by the dipping coating in step (4) in the transition layer solution, the immersion time is 45 minutes to 60 minutes, and 3 to 5 immersion and drying cycles are performed. After each immersion, use hot air drying in a well-ventilated environment at a temperature of 40 to 55° C. for 2 to 4 hours; The silicon carbide coating composition includes: 5 parts of tetraethyl orthosilicate, 4 parts of phenolic resin, and 1 part of nano carbon powder; After the transition layer is formed, the silicon carbide coating is applied.

[0015] Preferably, in step (5), after the transition layer is formed, the silicon carbide coating is applied according to the following steps: S1. Prepare a first layer of silicon carbide coating solution, add a transition layer component on the basis of the silicon carbide coating component, and add 12-15 parts of the transition layer component when the mass fraction of the silicon carbide coating component is 100 parts; S2. Stir and mix the transition layer components and the silicon carbide coating components in ethanol at a stirring speed of 300-450 r / min for 45-60 min. The mass fraction of the solution is 20%-50%. Apply the first layer of silicon carbide coating solution on the transition layer. S3, preparing a second layer of silicon carbide coating solution, reducing the added transition layer component to 7-10 parts, and correspondingly increasing the amount of silicon carbide coating components, keeping the total mass of the solution unchanged, and after preparing the solution, stirring according to the stirring conditions in step S2, and coating the second layer of silicon carbide coating solution on the first layer of silicon carbide coating; S4, prepare a third layer of silicon carbide coating solution, reduce the added transition layer component to 1-5 parts, and increase the amount of silicon carbide coating components accordingly, keeping the total mass of the solution basically unchanged. After preparing the solution, stir according to the stirring conditions in step S2, and apply the third layer of silicon carbide coating solution to the second layer of silicon carbide coating.

[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The hydrolyzed silane coupling agent in the present invention has higher activity and can more effectively serve as a bridge between the carbon fiber felt and the subsequent coating, making the carbon fiber felt and the coating more tightly bonded, thereby improving the structural integrity and mechanical properties of the entire composite material. The hydrolysis reaction fully disperses the silane coupling agent to form a small molecular structure, avoids agglomeration, ensures uniform distribution on the surface of the carbon fiber felt, ensures the uniformity of the subsequent coating, and makes the performance of the silicon carbide coating more stable and consistent; and the molecular size of the coupling agent after hydrolysis becomes smaller and the fluidity is enhanced, which is conducive to penetrating into the internal pores and fiber gaps of the carbon fiber felt, achieving uniform coupling, and providing a good foundation for the impregnation of the precursor solution and the uniform formation of the coating.

[0017] 2. The present invention can reduce the activity of silanol groups in the hydrolyzate, slow down the polycondensation reaction rate, prevent the premature formation of undesirable polymer structures, and maintain the activity and reactivity of the silane coupling agent by adding ethanol and ethylene glycol as stabilizers to the hydrolyzate; at the same time, the hydrolysis reaction balance is adjusted to avoid excessive hydrolysis and ensure sufficient effective ingredients; the wettability of the silane coupling agent solution to the carbon fiber felt is improved, the contact area is increased, the bonding force is improved, a transition layer is formed to reduce the interfacial tension, the adhesion between the carbon fiber felt and the subsequent coating is enhanced, the viscosity of the hydrolysis reaction system is adjusted, uniform dispersion during stirring and uniform distribution in subsequent operations are ensured, the reaction rate is moderate, and the stability and repeatability of the preparation process are improved.

[0018] 3. The present invention configures transition layer components (silane coupling agent containing epoxy group (KH-560), phenyl silicone resin, nano-silica particles) by weight, dissolves and disperses them in ethanol to form a transition layer solution, and performs multiple impregnation and drying cycles on the carbon fiber felt, which can not only utilize the advantages of each component (such as enhancing bonding strength, improving heat resistance, filling pores and enhancing barrier properties, etc.), but also enable the transition layer components to more fully penetrate into the interior and surface of the carbon fiber felt, forming a dense transition layer with a multi-layer structure.

[0019] 4. After the transition layer is formed, the present invention uses a unique layered preparation and coating process of the silicon carbide coating solution to gradually reduce the amount of transition layer components added and increase the amount of silicon carbide coating components from the first layer to the third layer, thereby achieving a gradual transition between the transition layer and the silicon carbide coating, avoiding sudden changes in performance between different layers, reducing internal stress and stratification problems, optimizing the coating structure, and forming a performance-optimized gradient structure from the inside to the outside of the coating, thereby significantly improving the overall performance of the material, including mechanical properties, chemical stability, heat resistance and wear resistance. DETAILED DESCRIPTION

[0020] The technical solutions in the present invention will be described clearly and completely below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] An embodiment provided by the present invention is a method for preparing a carbon fiber felt having a silicon carbide coating on its surface, comprising the following steps: (1) Pre-treating the carbon fiber felt by first washing it with an organic solvent and then drying it under the protection of an inert gas; (2) mixing the pretreated carbon fiber felt with the coupling agent solution so that the coupling agent is evenly distributed on the surface of the carbon fiber felt; (3) dissolving a silicon source and a carbon source in a solvent to form a precursor solution, wherein the molar ratio of the silicon source to the carbon source is 1:1-5; (4) impregnating the carbon fiber felt treated with the coupling agent in step (2) into the precursor solution prepared in step (3); (5) sequentially coating the transition layer component and the silicon carbide coating component onto the carbon fiber felt treated by dip coating in step (4); (6) subjecting the coated carbon fiber felt in step (5) to pyrolysis treatment under inert gas protection, with the pyrolysis temperature set at 1000-1500° C. and the pyrolysis time maintained at 1-5 h, so that the precursor is converted into a silicon carbide coating; (7) Curing the carbon fiber felt after pyrolysis in step (6).

[0022] In this embodiment, more specifically, in step (1), the organic solvent is ethanol, and the carbon fiber felt is completely immersed in the ethanol solution for 15-30 minutes.

[0023] In this embodiment, more specifically, in step (1), a drying furnace protected by inert gas is used, the cleaned carbon fiber felt is placed in the drying furnace, and the inert gas is continuously introduced to maintain an inert atmosphere in the furnace at a temperature of 50-100°C.

[0024] In this embodiment, more specifically, in step (2), the coupling agent solution is a silane coupling agent solution, and an amino-containing silane coupling agent (KH-550) is dissolved in ethanol, and stirred at a stirring speed of 200-500 r / min for 15-30 min to prepare a silane coupling agent solution with a mass fraction of 0.5%-5%, and the carbon fiber felt is immersed in the silane coupling agent solution for 0.5-2 h, and stirred at a speed of 50-100 r / min during the immersion process.

[0025] The present invention can significantly improve the chemical stability of the carbon fiber felt by preparing a silicon carbide coating on the surface of the carbon fiber felt. Silicon carbide itself has good chemical inertness and can effectively resist the erosion of chemical substances, so that the carbon fiber felt can maintain stable performance even in harsh chemical environments, broadening its application areas. For example, it can also be used in highly corrosive environments such as chemical and marine environments. The interface structure formed between the silicon carbide coating and the carbon fiber felt can effectively transfer stress, thereby improving the overall mechanical properties of the carbon fiber felt, such as tensile strength and bending strength. This allows the carbon fiber felt to better exert its material properties when subjected to external forces, and can be applied to aerospace, automobile manufacturing and other fields that have high requirements for material strength.

[0026] On the other hand, in step (1), the carbon fiber felt is first cleaned with an organic solvent such as ethanol, which can effectively remove oil stains, impurities, etc. on its surface, provide a clean surface for subsequent processing, and facilitate better adhesion of the subsequent coupling agent and uniform formation of the coating. Drying under the protection of inert gas can prevent the carbon fiber felt from being oxidized during the drying process, thereby ensuring the original performance of the carbon fiber felt. In step (2), the carbon fiber felt is treated with a coupling agent. The coupling agent can form a molecular film on the surface of the carbon fiber felt, one end of which is combined with the active group on the surface of the carbon fiber felt, and the other end has good affinity with the subsequent coated material, thereby greatly enhancing the bonding force between the carbon fiber felt and the subsequent coating, making the coating less likely to fall off, and improving the stability of the entire material structure. In step (7), the pyrolyzed carbon fiber felt is cured to further improve the structural stability and performance reliability of the material. After the curing treatment, the internal structure of the material is more compact, which helps to maintain the integrity and stability of the silicon carbide coating and ensure the quality of the final product.

[0027] In the above content of this embodiment, on the one hand, the carbon fiber felt and the silicon carbide coating are made of different materials, and the interface bonding force is often weak when directly combined. It is difficult for the silane coupling agent to form a strong covalent bond with the surface of the carbon fiber felt, and it mainly relies on weaker forces such as physical adsorption, resulting in the coupling agent not being firmly attached to the surface of the carbon fiber felt, and then the bonding force between the subsequent coating and the carbon fiber felt is insufficient. During use, the coating is prone to peeling and peeling, which affects the service life and performance of the product. On the other hand, the silane coupling agent is prone to agglomeration in the solution. When mixed with the carbon fiber felt, it is difficult to be evenly distributed on its surface, which will cause the coupling agent content at different parts of the carbon fiber felt surface to be different, so that the thickness and performance of the coating are uneven, affecting the overall quality and performance stability of the product. On the other hand, the silane coupling agent has a low reaction activity. In the subsequent interaction with the precursor solution, it cannot effectively promote the progress of various reactions, which may lead to insufficient penetration of the precursor solution, and incomplete reaction of the formation of the silicon carbide coating during the pyrolysis process, affecting the quality and performance of the coating, such as insufficient density and defects of the coating.

[0028] In order to solve the above problem, in this embodiment, more specifically, in the step (2), the coupling agent solution is a silane coupling agent solution. Before the solution is prepared, an aminosilane coupling agent (KH-550) is added to a mixed solution of isopropanol and water for hydrolysis reaction, the volume ratio of alcohol to water is 2:1, the stirring speed is 400-500 r / min, the stirring time is 30-60 min, and the reaction temperature is between 30-40°C; and hydrochloric acid is added as a catalyst, and the amount of the catalyst added is 0.5%-0.7% of the mass of the silane coupling agent.

[0029] In this embodiment, the silane coupling agent will generate active groups such as silanol groups after the hydrolysis reaction, so as to react chemically with the hydroxyl groups on the surface of the carbon fiber felt to form covalent bonds, so that the coupling agent is more firmly bonded to the surface of the carbon fiber felt. Compared with the unhydrolyzed coupling agent, the bonding force with the carbon fiber felt is greatly enhanced, and the adhesion stability of the coating is improved. The hydrolyzed silane coupling agent has higher activity and can more effectively serve as a bridge between the carbon fiber felt and the subsequent coating, making the bonding between the carbon fiber felt and the coating tighter, and improving the structural integrity and mechanical properties of the entire composite material.

[0030] On the other hand, the hydrolysis reaction makes the silane coupling agent fully dispersed in the solution and form a small molecular structure. When mixed with the carbon fiber felt, it can be more evenly distributed on the surface of the carbon fiber felt, avoiding the agglomeration of the coupling agent, thereby ensuring the uniformity of the subsequent coating on the surface of the carbon fiber felt, making the performance of the silicon carbide coating more stable and consistent. The molecular size of the hydrolyzed silane coupling agent becomes smaller, the fluidity is enhanced, and it is easier to penetrate into the internal pores and fiber gaps of the carbon fiber felt, achieving a uniform coupling effect in the entire thickness direction of the carbon fiber felt, which is conducive to the subsequent impregnation of the precursor solution and the uniform formation of the coating, and improving the uniformity of the overall performance of the material. On the other hand, the interface layer formed by the hydrolyzed silane coupling agent on the surface of the carbon fiber felt has good chemical stability, which can isolate the direct contact between the carbon fiber felt and the external environment, prevent the carbon fiber felt from being eroded by external chemicals, and also provide a stable foundation for the subsequent silicon carbide coating, which helps to improve the chemical stability and service life of the entire composite material. The chemical bonds and interface structures formed after the hydrolysis of the silane coupling agent can improve the bonding tightness between the carbon fiber felt and the silicon carbide coating, reduce the defects and pores in the coating, thereby enhancing the resistance of the composite material to corrosive media and making it have better corrosion resistance in harsh chemical environments.

[0031] In the above content of the present embodiment, silanol groups will be produced after the hydrolysis of the silane coupling agent, and these active groups are prone to polycondensation in the absence of a stabilizer. The polycondensation reaction will cause the formation of larger polymers between the silane coupling agent molecules, which may make the solution turbid, or even produce precipitation, reduce the activity of the silane coupling agent solution, and thus affect its reaction effect with the surface of the carbon fiber felt. The solution may become too viscous or too thin, and it is difficult to be evenly distributed on the carbon fiber felt in the subsequent mixing and impregnation steps, affecting the quality of the coating and the performance consistency of the final product. Without a stabilizer, the storage stability of the hydrolyzate will be reduced, and its effective activity retention time is short, and it cannot be stored for a long time.

[0032] In order to solve the above problem, in this embodiment, more specifically, in the step (2), ethanol and ethylene glycol are added to the hydrolyzate as stabilizers, firstly ethanol is added in an amount of 7%-8% of the volume of the hydrolyzate, and stirred evenly at a stirring speed of 450 r / min for 10-15 min; then ethylene glycol is added in an amount of 10%-12% of the volume of the hydrolyzate, and stirring is continued during the addition process.

[0033] In this embodiment, by adding ethanol and ethylene glycol to the hydrolyzate, on the one hand, the activity of the silanol group after hydrolysis can be reduced, the speed of the polycondensation reaction can be slowed down, and the polycondensation can be prevented from occurring prematurely in the subsequent treatment process to form an undesirable polymer structure, thereby ensuring that the silane coupling agent can maintain good activity and reactivity when it subsequently acts with the carbon fiber felt. Ethanol and ethylene glycol can adjust the balance of the hydrolysis reaction to a certain extent, avoiding excessive hydrolysis of the silane coupling agent, which may cause the loss of the effective ingredients of the silane coupling agent and affect its bonding effect with the carbon fiber felt, while the presence of ethanol and ethylene glycol helps to maintain the hydrolysis reaction at an appropriate level, ensuring that the silane coupling agent has enough effective ingredients to play a role.

[0034] On the other hand, ethanol and ethylene glycol have good solubility and surface activity, which can improve the wettability of the silane coupling agent solution to the carbon fiber felt, so that the silane coupling agent solution can better penetrate into the interior of the carbon fiber felt and be evenly distributed on the surface of the carbon fiber, thereby increasing the contact area between the silane coupling agent and the carbon fiber and improving the bonding force. Ethanol and ethylene glycol can form a transition layer between the hydrolyzate of the silane coupling agent and the carbon fiber, reduce the interfacial tension, improve the bonding strength between the two, and then enhance the adhesion between the carbon fiber felt and the subsequent coating, and improve the performance of the entire composite material. On the other hand, the addition of ethanol and ethylene glycol can adjust the viscosity of the hydrolysis reaction system. The appropriate viscosity is conducive to the uniform dispersion of the silane coupling agent during the stirring process, and the uniform distribution of the solution in the carbon fiber felt in the subsequent operations such as dipping. If the viscosity is not appropriate, it may cause the solution to be unevenly distributed in the carbon fiber felt, affecting the quality and performance of the coating. Ethanol and ethylene glycol can make the entire reaction system at a suitable reaction rate, while ensuring that the reaction is fully carried out, avoiding quality problems caused by too fast or too slow reaction, which is conducive to improving the stability and repeatability of the preparation process.

[0035] In this embodiment, more specifically, in step (3), the silicon source is tetraethyl orthosilicate, the carbon source is sucrose, and the solvent is at least two of ethanol, isopropanol, and water; a container with a stirring function is used to hold the solvent, and tetraethyl orthosilicate and sucrose are added to the solvent at a stirring speed of 400-500 r / min and a stirring time of 45-60 min.

[0036] This embodiment uses tetraethyl orthosilicate and sucrose as silicon source and carbon source respectively, which has the advantages of wide sources, low cost, stable properties, etc., and can provide sufficient elements for the formation of silicon carbide. At the same time, the use of at least two solvents, ethanol, isopropanol, and water, can optimize the solubility of the precursor by utilizing the characteristics of good solubility and moderate volatility of different solvents. In addition, the stirring speed of 400-500r / min and the stirring time of 45-60min can ensure that the silicon source and the carbon source are fully dissolved and mixed, ensuring that the precursor solution is uniform, which is conducive to the uniform quality of the subsequent coating.

[0037] In the present embodiment, more specifically, in the step (5), the transition layer components include, by weight, 2 parts of an epoxy-containing silane coupling agent (KH-560), 6 parts of a phenyl silicone resin, and 2 parts of nano-silica particles; the transition layer components are dissolved and dispersed in ethanol to form a transition layer solution, and the carbon fiber felt treated by the dip coating in the step (4) is dipped in the transition layer solution for 45 min-60 min, and 3-5 dip and drying cycles are performed. After each dip, hot air drying is performed in a well-ventilated environment at a temperature of 40-55°C for 2-4 h. The silicon carbide coating components include: 5 parts of tetraethyl orthosilicate, 4 parts of a phenolic resin, and 1 part of a nano-carbon powder; after the transition layer is formed, the silicon carbide coating is applied.

[0038] In this embodiment, more specifically, in step (5), after the transition layer is formed, the silicon carbide coating is applied according to the following steps: S1. Prepare a first layer of silicon carbide coating solution, add a transition layer component on the basis of the silicon carbide coating component, and add 12-15 parts of the transition layer component when the mass fraction of the silicon carbide coating component is 100 parts; S2. Stir and mix the transition layer components and the silicon carbide coating components in ethanol at a stirring speed of 300-450 r / min for 45-60 min. The mass fraction of the solution is 20%-50%. Apply the first layer of silicon carbide coating solution on the transition layer. S3, preparing a second layer of silicon carbide coating solution, reducing the added transition layer component to 7-10 parts, and correspondingly increasing the amount of silicon carbide coating components, keeping the total mass of the solution unchanged, and after preparing the solution, stirring according to the stirring conditions in step S2, and coating the second layer of silicon carbide coating solution on the first layer of silicon carbide coating; S4, prepare a third layer of silicon carbide coating solution, reduce the added transition layer component to 1-5 parts, and increase the amount of silicon carbide coating components accordingly, keeping the total mass of the solution basically unchanged. After preparing the solution, stir according to the stirring conditions in step S2, and apply the third layer of silicon carbide coating solution to the second layer of silicon carbide coating.

[0039] In this embodiment, the epoxy-containing silane coupling agent (KH-560) can play a good bridging role between the carbon fiber felt and the silicon carbide coating. Through the activity of the epoxy group, it can react chemically with the active groups left on the surface of the carbon fiber felt after the coupling agent treatment, and it can also have good compatibility with the subsequent coating components, thereby enhancing the bonding force between the transition layer and the carbon fiber felt. Phenyl silicone resin can bring good heat resistance and weather resistance to the transition layer. In the subsequent pyrolysis and use process, it can withstand the test of high temperature and complex environment, and prevent the performance of the carbon fiber felt from decreasing at high temperature. Phenyl silicone resin can fill the microscopic pores and defects on the surface of the carbon fiber felt, provide a smoother and more uniform substrate for the subsequent silicon carbide coating, and facilitate the uniform coating and adhesion of the silicon carbide coating. Nano-silicon dioxide particles can increase the hardness and wear resistance of the transition layer and improve the mechanical properties of the material. The nano-scale size can be evenly dispersed in the transition layer, microscopically enhance the structure of the transition layer, form a denser structure, improve the barrier properties of the transition layer, and reduce the impact of the external environment on the carbon fiber felt.

[0040] On the other hand, by adjusting the composition ratio of the transition layer and the silicon carbide coating layer by layer, the amount of the transition layer component added is gradually reduced and the amount of the silicon carbide coating component is correspondingly increased in the preparation of the silicon carbide coating solution from the first layer to the third layer, so as to achieve a gradual transition between the transition layer and the silicon carbide coating, avoid the sudden change of performance between different layers, make the transition smoother, and reduce the internal stress and delamination problems caused by the large difference in interface performance. This composition adjustment method can optimize the coating structure. On the side close to the transition layer, the presence of the transition layer component helps to enhance the bonding force, while the silicon carbide coating component close to the outside gradually increases, ensuring the main performance of the outer silicon carbide coating, so that the coating forms a gradient structure with optimized performance from the inside to the outside, and improves the overall performance of the material. In summary, step (5) can improve the performance of the material, enhance the bonding force between the layers, and form a silicon carbide coated carbon fiber felt with stable structure and good performance by optimizing the transition layer composition, impregnation and drying process, and coating and composition adjustment of the silicon carbide coating, so as to make it have better mechanical properties, chemical stability, heat resistance and wear resistance.

[0041] Comparative Example 1: The only difference between Comparative Example 1 and Example 1 is that in step (2), no ethanol or ethylene glycol is added to the hydrolyzate.

[0042] Comparative Example 2: The only difference between Comparative Example 2 and Example 1 is that in step (2), ethanol is added to the hydrolyzate as a stabilizer instead of ethylene glycol.

[0043] Comparative Example 3: The only difference between Comparative Example 3 and Example 1 is that in step (5), after the transition layer is formed, a silicon carbide coating without transition layer components is directly applied.

[0044] The following are the performance experimental data of the carbon fiber felt with silicon carbide coating on the surface prepared according to the preparation methods provided in the above embodiments and comparative examples: Experiment number Bonding strength between silicon carbide coating and carbon fiber felt Silicon Carbide Coating Uniformity Silicon carbide coating hardness Silicon carbide coating corrosion resistance Thermal shock resistance of silicon carbide coating Example 1 powerful good high good good Comparative Example 1 Weaker (because the hydrolysis product is unstable, resulting in decreased binding strength) Poor (prone to unevenness) Lower (coating defective) Poor (weak interface bonding, affecting corrosion resistance) Poor (weak bonding and easy to be damaged) Comparative Example 2 Medium (weaker than Example 1, slightly less stable) Medium (some unevenness) Medium (coating performance slightly affected) Medium (corrosion resistance reduced) Moderate (thermal shock resistance affected) Comparative Example 3 Moderate (lack of optimized bonding effect of transition layer) General (stratification occurs) Medium (optimized structure without transition layer) Moderate (corrosion resistance affected) Moderate (reduced thermal shock resistance) The above experimental data show that in terms of the bonding strength between the silicon carbide coating and the carbon fiber felt, in Example 1, ethanol and ethylene glycol are added as stabilizers in step (2), which ensures the stability of the hydrolyzate. At the same time, the design of a complete transition layer and a multi-layer silicon carbide coating makes the bonding strength between the coating and the carbon fiber felt strong. However, since no stabilizer is added to Comparative Example 1, the stability of the hydrolyzate may lead to a decrease in bonding strength; Comparative Example 2 only adds ethanol as a stabilizer, and the stability is slightly inferior to that of Example 1, so the bonding strength will also be reduced accordingly; Comparative Example 3 lacks the optimization of the bonding strength by the transition layer components, resulting in a medium bonding strength.

[0045] In terms of the uniformity of the silicon carbide coating: Example 1 ensures the uniformity of the coating through reasonable preparation steps, including the addition of a stabilizer in step (2) to ensure the stability of the coupling agent solution and the careful operation of the multi-layer transition layer and the silicon carbide coating in step (5). Comparative Example 1 may have unevenness due to the lack of a stabilizer; Comparative Example 2 may cause partial unevenness due to the lack of ethylene glycol; Comparative Example 3 may have unevenness such as stratification due to direct coating.

[0046] In terms of the hardness of the silicon carbide coating: the optimization of the multilayer structure and composition in Example 1 will result in a higher hardness of the coating, while in the comparative example, due to changes in various conditions, the integrity and structure of the coating are affected, and the hardness is reduced accordingly.

[0047] In terms of the corrosion resistance of the silicon carbide coating: Example 1 forms a stable structure and a good interface through complete steps, and has good corrosion resistance. Different changes in conditions in the comparative example will affect the integrity and interface of the coating, thereby reducing the corrosion resistance.

[0048] In terms of thermal shock resistance of silicon carbide coating: the good structure and interface of Example 1 ensure its stability in a thermal shock environment, while the comparative example is easily damaged in a thermal shock environment due to imperfect structure or interface, and its thermal shock resistance decreases.

[0049] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A method for preparing a carbon fiber felt having a silicon carbide coating on the surface, characterized in that: The following steps are involved: (1) Pre-treating the carbon fiber felt by first washing it with an organic solvent and then drying it under the protection of an inert gas; (2) Mixing the pretreated carbon fiber felt with the coupling agent solution so that the coupling agent is evenly distributed on the surface of the carbon fiber felt; (3) dissolving a silicon source and a carbon source in a solvent to form a precursor solution, wherein the molar ratio of the silicon source to the carbon source is 1:1-5; (4) impregnating the carbon fiber felt treated with the coupling agent in step (2) into the precursor solution prepared in step (3); (5) sequentially coating the transition layer component and the silicon carbide coating component onto the carbon fiber felt treated by dip coating in step (4); (6) subjecting the coated carbon fiber felt in step (5) to pyrolysis treatment under inert gas protection, with the pyrolysis temperature set at 1000-1500° C. and the pyrolysis time maintained at 1-5 h, so that the precursor is converted into a silicon carbide coating; (7) Curing the carbon fiber felt after pyrolysis in step (6).

2. The method for preparing a carbon fiber felt having a silicon carbide coating on the surface according to claim 1, characterized in that: In the step (1), the organic solvent is ethanol, and the carbon fiber felt is completely immersed in the ethanol solution for 15-30 minutes.

3. The method for preparing a carbon fiber felt having a silicon carbide coating on the surface according to claim 2, characterized in that: In the step (1), a drying furnace protected by inert gas is used, the cleaned carbon fiber felt is placed in the drying furnace, and the inert gas is continuously introduced to maintain an inert atmosphere in the furnace at a temperature of 50-100°C.

4. The method for preparing a carbon fiber felt having a silicon carbide coating on the surface according to claim 1, characterized in that: In the step (2), the coupling agent solution is a silane coupling agent solution, and an amino-containing silane coupling agent (KH-550) is dissolved in ethanol, and stirred at a stirring speed of 200-500 r / min for 15-30 min to prepare a silane coupling agent solution with a mass fraction of 0.5%-5%. The carbon fiber felt is immersed in the silane coupling agent solution for 0.5-2 h, and stirred at a speed of 50-100 r / min during the immersion process.

5. The method for preparing a carbon fiber felt having a silicon carbide coating on the surface according to claim 1, characterized in that: In the step (2), the coupling agent solution is a silane coupling agent solution. Before the solution is prepared, an aminosilane coupling agent (KH-550) is added to a mixed solution of isopropanol and water for hydrolysis reaction, the volume ratio of alcohol to water is 2:1, the stirring speed is 400-500 r / min, the stirring time is 30-60 min, and the reaction temperature is between 30-40°C; and hydrochloric acid is added as a catalyst, and the amount of the catalyst added is 0.5%-0.7% of the mass of the silane coupling agent.

6. The method for preparing a carbon fiber felt having a silicon carbide coating on the surface according to claim 5, characterized in that: In the step (2), ethanol and ethylene glycol are added to the hydrolyzate as stabilizers. Ethanol is first added in an amount of 7%-8% of the volume of the hydrolyzate, and stirred evenly at a stirring speed of 450 r / min for 10-15 min. Ethylene glycol is then added in an amount of 10%-12% of the volume of the hydrolyzate, and stirring is continued during the addition process.

7. The method for preparing a carbon fiber felt having a silicon carbide coating on the surface according to claim 1, characterized in that: In the step (3), the silicon source is tetraethyl orthosilicate, the carbon source is sucrose, and the solvent is at least two of ethanol, isopropanol, and water; a container with a stirring function is used to hold the solvent, and tetraethyl orthosilicate and sucrose are added to the solvent at a stirring speed of 400-500 r / min and a stirring time of 45-60 min.

8. The method for preparing a carbon fiber felt having a silicon carbide coating on the surface according to claim 1, characterized in that: In the step (5), the transition layer comprises, by weight: 2 parts of epoxy-containing silane coupling agent (KH-560), 6 parts of phenyl silicone resin, and 2 parts of nano-silicon dioxide particles; Dissolve the transition layer components in ethanol to form a transition layer solution, immerse the carbon fiber felt treated by the dipping coating in step (4) in the transition layer solution, the immersion time is 45 minutes to 60 minutes, and 3 to 5 immersion and drying cycles are performed. After each immersion, use hot air drying in a well-ventilated environment at a temperature of 40 to 55° C. for 2 to 4 hours; The silicon carbide coating composition includes: 5 parts of tetraethyl orthosilicate, 4 parts of phenolic resin, and 1 part of nano carbon powder; After the transition layer is formed, the silicon carbide coating is applied.

9. The method for preparing a carbon fiber felt having a silicon carbide coating on the surface according to claim 8, characterized in that: In step (5), after the transition layer is formed, the silicon carbide coating is applied according to the following steps: S1. Prepare a first layer of silicon carbide coating solution, add a transition layer component on the basis of the silicon carbide coating component, and add 12-15 parts of the transition layer component when the mass fraction of the silicon carbide coating component is 100 parts; S2. Stir and mix the transition layer components and the silicon carbide coating components in ethanol at a stirring speed of 300-450 r / min for 45-60 min. The mass fraction of the solution is 20%-50%. Apply the first layer of silicon carbide coating solution on the transition layer. S3, preparing a second layer of silicon carbide coating solution, reducing the added transition layer component to 7-10 parts, and correspondingly increasing the amount of silicon carbide coating components, keeping the total mass of the solution unchanged, and after preparing the solution, stirring according to the stirring conditions in step S2, and coating the second layer of silicon carbide coating solution on the first layer of silicon carbide coating; S4, prepare a third layer of silicon carbide coating solution, reduce the added transition layer component to 1-5 parts, and increase the amount of silicon carbide coating components accordingly, keeping the total mass of the solution basically unchanged. After preparing the solution, stir according to the stirring conditions in step S2, and apply the third layer of silicon carbide coating solution to the second layer of silicon carbide coating.

10. A carbon fiber felt having a silicon carbide coating on its surface, prepared by the method for preparing a carbon fiber felt having a silicon carbide coating on its surface according to any one of claims 1 to 9.